Timed Concurrent Constraint Programming for Analysing Biological Systems - Gutiérrez, Julian; Pérez, Jorge A.; Rueda, Camilo; Valencia, Frank D. (Electronic notes in theoretical computer science, 2007)
In this paper we present our first approach to model and verify biological systems using ntcc, a concurrent constraint process calculus. We argue that the partial information constructs in ntcc can provide a suitable language for such systems. We also illustrate how ntcc may provide a unified framework for the analysis of biological systems, as they can be described, simulated and verified using the elements provided by the calculus.